THE IMPACT OF ONLINE LEARNING ON THE LEARNING MOTIVATION OF PRIMARY SCHOOL STUDENTS - Rizka Alfarimba; Sekar Dwi Ardianti; Khamdun Khamdun (PROGRES PENDIDIKAN, 2021)
This study aims to describe the learning motivation of grade 5 students in Gondosari village as a result of the implementation of online learning during the covid-19 pandemic. This research uses the descriptive qualitative method. The objects of this study are 6 students of grade with the categorization of rank, their parents' educational background, and their parent’s occupation and 1 classroom teacher who teach online in grade 5 of SD 7 Gondosari village. With observation, semi-structured interviews, and documentation as tools for data collection. The validity test of this study used triangulation of online learning has an impact on students learning motivation with indicators of learning motivation, namely perseverance in facing tasks, resilience in facing difficulties, interest in various problems, working independently, and factors from the learning environment. This indicator can measure the extent to which the learning motivation of grade 5 students of SD 7 Gondosari.